Unintended Effects of Risk Communication: Impacts of Message Fatigue, Risk Tolerance, and Trust in Public Health Information on Psychological Reactance (Journal of International Crisis and Risk Communication Research, 2021)
How individuals experience unintended effects of risk messages is an understudied area. Focusing on three types of unintended effects (i.e., message fatigue, risk tolerance, and psychological reactance) associated with health risk communication, we conducted an online survey among Italian adults (N = 507) to investigate how perceived message fatigue and risk tolerance might induce psychological reactance and whether trust in public health information might mediate this relationship. Results from mediation models revealed: (a) greater message fatigue and risk tolerance increased psychological reactance; (b) greater message fatigue and risk tolerance led to distrust in government-shared health information; (c) trust in public health information mediated the effects of message fatigue and risk tolerance on psychological reactance. Theoretical and practical implications are discussed.